The So-Called Pan-European Depositors' Protection Scheme: A Further Euro Own-Goal? A Critical Analysis of Directive 2014/49. Issue 2 (April 2016) - de Gioia-Carabellese, Pierre; Chessa, Corrado
This article focuses on the legal provisions of Directive 2014/49 on deposit guarantee schemes (the DGS Directive) and focuses on how the national schemes financially support each another by offering a critical analysis to demonstrate that the new legal framework is far from satisfactory. This is because the new 'safety net', still hinged on depositors' protections schemes that operate at the national level, is fettered by the quantitative limits and legal constraints of mutual borrowing. This ultimately still leaves the EU/EEA depositors with an element of uncertainty. This contribution also seeks to illustrate that the recent mass withdrawal from bank deposits in Greece (in June/July 2015) was an unsuccessful test case for the new legislation, which was ironically already in force at the time the crisis unfolded. This case study of Greece is coupled with the important Landslaki dictum which is given equal attention in this article. Together they give significant credibility to the view that the DGS Directive, seemingly not fully aware of the lessons to be learnt from the 2011 Eurozone crisis, is obsolete and should be amended as soon as possible.